Student experiences of nursing education in shaping character: A phenomenological study - Edison Kabak (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Character building is an important aspect of nursing education to produce competent and ethical professional nurses. Nursing education emphasizes not only technical skills but also the development of moral values and leadership. Purpose: To explore the experiences of nursing students in shaping character through nursing education. Method: A phenomenological approach was used by conducting in-depth interviews with ten nursing students. The data were analyzed thematically to identify the experiences and processes of character formation. Results: Show that the formation of partisipants character is a dynamic process involving four main aspects: clinical practice experience, self-reflection, social interaction and organizational activities, and internalization of moral and ethical values. Practical experience builds responsibility and decision-making, self-reflection increases professional awareness, social interaction hones communication and leadership skills, while moral values become the ethical foundation. Conclusion: Nursing education must integrate practice, reflection, social interaction, and moral values to form students who are competent as well as characterful and ethical.